Service and route design of shuttle service for university employees in UP Diliman - Benales, Emmanuel Jr. L.; Casalme, Van Joseph E. (College of Engineering, University of the Philippines Diliman, 2015)
Employees living in off-campus housings generally spend more compared to residents of on-campus housings since they have higher transportation expenses. A proposed solution to this existing gap in living conditions is the implementation of a free shuttle service that will serve off-campus residents. A shuttle service is a point-to-point demand-responsive transit traversing a route which is generally short and as direct as possible. The aim of this study is to determine the most efficient service and route design for the proposed shuttle service in terrns of travel cost savings. The results of a recent survey, with 741 respondents, were used in the design. Data about the population size were unavailable during the study so the design was solely based on the sample size. Five shuttle routes, with their corresponding stops, were identified after analyzing the trip patterns of the respondents. Schedules of shuttle arrivals at each station were also generated. The average travel cost for one-way trip by university employees was found to be Php 52.50. After computing the estimated travel cost savings of each respondent, the shuttle service was found to reduce the average travel cost of the sample by 52%. The estimated cost of implementation is around Php 2.2M to Php 3.08M per bus. The implementation may have to be done one route at a time since the cost of one bus is high. A better estimate of the operating cost of the shuttle can be made if a study is conducted on actual costs.